Prospects of Halal Industry in Indonesia: Literacy and Inclusion of Halal Products - Ismanto, Kuat; Farmawati, Ira (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This research aims to map the literacy and inclusion of halal products in Muslim communities and their impact on the halal industry in Indonesia. The design of this research is a field study with a mixed approach (descriptive quantitative-qualitative). The population of this research is the local residence in general and the academic community of Islamic universities in particular. The number of research respondents was 103 people obtained from distributing questionnaires via Google Forms. Because the population size is unknown, the sample was determined using the Lameshow model based on the convenience sample. From the data processing, it was concluded that literacy and inclusion of halal products among the public were categorized as high—aspects of knowledge of halal ingredients, halal products, and halal labels in the high category. Respondents' understanding and knowledge of